Features of the design of exposition spaces in art centers - O. Kostyuchenko (теорія та практика дизайну, 2017)
The article deals with the features of the representation of contemporary art in the exposition spaces of art centers. The work reveals the features of modern art and their influence on the organization of the exhibition space. Historical development of approaches to the organization of space for exhibiting works of contemporary art from approaches related to technological conditions and a historically authentic environment to exhibition spaces that acquire the features of an independent work of art is given. Determined new conceptual approaches to the formation of exhibition space, which is based on the idea of fusion of art and space stsenarnosti exhibition space, curator of exhibitions and influence the interaction between artists, art and audience. This will allow the most effective demonstration of works of contemporary art in art centers.